Digital-Immigrant Lecturers’ Perceived Easiness About and Acceptance towards E-Learning during the Pandemic Era - Jefri Marzal; Nizlel Huda; Muhammad Haris Effendi Hsb (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
Most of digital immigrant lecturers (DILs) in university possess good perceived usefulness but at some extent they hold low perceived easiness towards e-learning portals such as the LMS. This study aimed to analyses the digital-immigrant lecturers’ perceived easiness about e-learning portals and the relationship between the perception and their acceptance towards the portals. This study used survey and experimental research designs. The subjects of this study involve 78 participants of the University students of information communication technology peer-tutorial training. A questionnaire was used to collect the data, during the training they were encouraged to express their perceived easiness about and acceptance towards the portals via a questionnaire. Data were analyzed using the Wilcoxon test and the Spearman rho correlation test. The results of the analysis show that the peer-tutorial training increases the digital-immigrant lecturers’ perceived easiness about the portals. The results also show there is a significant correlation between the perceived easiness and their acceptance towards the portals. It seems that the training is effective in promoting the digital-immigrant lecturers’ perceived easiness about the e-learning portals which is significantly contributive to their acceptance to use them.